Supercritical carbon dioxide (SC-CO2) extraction of catechin, epicatechin, rutin and luteolin from spearmint (Mentha spicata L.) leaves - Bimakr, Mandana; Abdul Rahman, Russly; Taip, Farah Saleena; Ling, Tau Chuan; Ganjloo, Ali; Md Salleh, Liza; Selamat, Jinap; Abdul Hamid, Azizah (IDOSI Publications, 2008)
In this study, supercritical carbon dioxide (SC-CO2) extraction conditions were optimized for the simultaneous separation of four bioactive flavonoids (catechin, CA; epicatechin, EP; rutin, RU; luteolin, LU) contained in spearmint (Mentha spicata L.) leaves. SC-CO2 extraction parameters such as pressure, temperature and dynamic extraction time were optimized by Complete Randomize Design (CRD) full factorial. The optimum condition of SC-CO2 extraction was achieved at 200 bar, 60°C and 60 min (with 60.566 mg/g extraction yield). Extracted yield at optimum condition was then analyzed by high performance liquid chromatography (HPLC) for quantifying bioactive flavonoid compounds. At optimum conditions, four bioactive flavonoids including (+)-catechin, (-)-epicatechin, rutin and luteolin were detected at high concentration. Luteolin (0.657 mg/g) had the highest concentration among the other detected flavonoids. The results indicated that SC-CO2 extraction is a promising and alternative process for recovering the bioactive compounds from spearmint leaves.